Struktury procesowe i zadaniowe : analiza porównawcza - Lichtarski, Janusz Marek (Process and Task Structures : Comparative Analysis, 2009)
Process and task structures became more and more popular both in theory and practice of management. There are many various approaches and definitions in the literature, which present process and task structures like very similar or totally different organizational solutions. The goal of the article is to present comparative analysis of those types of structures. Many similarities and common elements as well as differences were shown in the study. Due to the temporary nature of task structures they are seen as more complex and complicated. The article is based on literature study and the results of author's own questionnaire findings and case studies. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 404-412